2021
DOI: 10.1021/acs.analchem.0c04471
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Flight Secondary Ion Mass Spectrometry Imaging of Cross Sections from the Bacchanals Paintings of Nicolas Poussin

Abstract: The two paintings Infant Bacchanals (Museo Nazionale d'Arte Antica, Palazzo Barberini, Rome, Italy) executed by Nicolas Poussin (Les Andelys, 1594 -Rome, 1665) in around 1626, are thought to have been painted "a guazzo", which means either with a glue or with an egg binding medium. To date, this has never been confirmed through analysis. Dual beam Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS), using a bismuth cluster liquid metal ion gun and an argon gas cluster ion beam, allows the mapping of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…As an example, ToF‐SIMS was recently applied to chemically image cross‐sections of two 17th century paintings by Nicolas Poussin in order to determine the binding medium used. The results obtained by ToF‐SIMS suggested that an oil‐based binder rather than an egg‐based binder was likely used 167 . The data from ToF‐SIMS depth profiling are complementary to those acquired from workhorse characterization tools such as XRR and NR, although the depth resolution is poorer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, ToF‐SIMS was recently applied to chemically image cross‐sections of two 17th century paintings by Nicolas Poussin in order to determine the binding medium used. The results obtained by ToF‐SIMS suggested that an oil‐based binder rather than an egg‐based binder was likely used 167 . The data from ToF‐SIMS depth profiling are complementary to those acquired from workhorse characterization tools such as XRR and NR, although the depth resolution is poorer.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by ToF-SIMS suggested that an oil-based binder rather than an egg-based binder was likely used. 167 The data from ToF-SIMS depth profiling are complementary to those acquired from workhorse characterization tools such as XRR and NR, although the depth resolution is poorer. There may be opportunities to use the "real-space" data from ToF-SIMS to reduce uncertainty in the analysis of reciprocal-space data from scattering and reflectivity.…”
Section: Depth Profilingmentioning
confidence: 99%
“…MSI is extensively used for biological applications, but it also proved useful in other fields: in forensics to reconstitute fingerprints 34 or search for drugs of abuse in low amounts of hair 35 ; in art to study old paintings without invasive protocols 33 , in materials analysis to search for surface irregularities 36 . As in the cited applications, the present study demonstrates the ability of MSI to bring additional information on the samples of interest without a biological background.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of the mass spectrum from the ROI associated with a specific layer and its comparison with reference spectra can directly provide the type of binder used for this layer, or an estimate of the origin of the glue, or the type of oil by using peak intensity ratios. 11,50,83 This can replace destructive methods like GC-MS, and these ratios are obtained in a spatially resolved fashion.…”
Section: Paintingsmentioning
confidence: 99%
“…As an example, the potential at the surface of a painting sample embedded in a several mm thick resin block can differ by several hundred volts, whereas the applied extraction voltage is 2 kV. This fine tuning of the mass analyzer was studied by Seyer et al with plant tissues,82 and a detailed study of the implications of this phenomenon on painting cross sections was recently published by Bouvier et al11 A former possible method to avoid variations in the extraction field was to place a slotted stainless steel plate on the analyzed surface of cross section, which has the benefit to keep a part of the surface conduc-…”
mentioning
confidence: 99%